Use of Quantitative PCR Detection Methods to Study Biocontrol Agents and Phytopathogenic Fungi and Oomycetes in Environmental Samples. Issue 1 (8th July 2013) - Sanzani, Simona M.; Li Destri Nicosia, Maria G.; Faedda, Roberto; Cacciola, Santa O.; Schena, Leonardo
Abstract Quantitative polymerase chain reaction (qPCR) is a versatile technique for the accurate, sensitive, reliable and high‐throughput detection and quantification of target DNA in various environmental samples, and in recent years, it has greatly contributed to the advancement of knowledge in the plant pathology field. Indeed, this technique is ideal to evaluate inoculum threshold levels and to study the epidemiology, biology and ecology of phytopathogenic fungi and oomycetes, thus opening up new research opportunities to investigate host–pathogen interactions and to address tasks related to quarantine, eradication and biosecurity. Moreover, it can be a useful tool in breeding programs. The present review analyses the most relevant applications of qPCR for the detection and quantification of filamentous fungi and oomycetes within host tissues and in soil, air and water, along with brief paragraphs focusing on new application fields such as the detection and quantification of mycotoxigenic fungi and biocontrol agents. The high potentiality of qPCR for present and future applications is highlighted together with a critical analysis of major drawbacks that need to be corrected to definitively confirm it as a preferential routine quantitative detection method.